Multimodal optical contrast agents as new tools for monitoring and tuning nanoemulsion internalisation into cancer cells. From live cell imaging to in vivo imaging of tumours. Issue 4 (13th March 2020) - Prévot, Geoffrey; Bsaibess, Talia; Daniel, Jonathan; Genevois, Coralie; Clermont, Guillaume; Sasaki, Isabelle; Marais, Sebastien; Couillaud, Franck; Crauste-Manciet, Sylvie; Blanchard-Desce, Mireille
Abstract : Tailor-made NIR emitting dyes were designed as multimodal optical probes. Abstract : Tailor-made NIR emitting dyes were designed as multimodal optical probes. These asymmetric amphiphilic compounds show combined intense absorption in the visible region, NIR fluorescence emission, high two-photon absorption in the NIR (with the maximum located around 1000 nm) as well as large Stokes' shift values and second-harmonic generation ability. Thanks to their structure, high loading into nanoemulsions (NEs) could be achieved leading to very high one- and two-photon brightness. These dyes were demonstrated to act as multimodal contrast agents able to generate different optical modalities of interest for bioimaging. Indeed, the uptake and carrier behaviour of the dye-loaded NEs into cancer cells could be monitored by simultaneous two-photon fluorescence and second-harmonic generation optical imaging. Multimodal imaging provided deep insight into the mechanism and kinetics of dye internalisation. Quite interestingly, the nature of the dyes was also found to influence both the kinetics of endocytosis and the internalisation pathways in glioblastoma cancer cells. By modulating the charge distribution within the dyes, the NEs can be tuned to escape lysosomes and enter the mitochondria. Moreover, surface functionalization with PEG macromolecules was realized to yield stealth NIRF-NEs which could be used for in vivo NIRF imaging of subcutaneous tumours in mice.